Pengaruh Penggunaan Fitur Live Streaming terhadap Keputusan Pembelian Konsumen pada Aplikasi TikTok: pada Mahasiswa Ekonomi Syariah STAI Sangatta - Raniati Tepu; Imrona Hayati; Ajis Supangat (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The TikTok application, which now offers the TikTok Shop feature, is one example of how significant changes in the digital commerce industry have been fueled by information technology advancements. This feature creates a real-time interactive experience by enabling customers to shop directly through live broadcasting. The purpose of this study is to examine how using the live streaming feature affects purchasing decisions, particularly for students at STAI Sangatta. 64 students enrolled in STAI Sangatta's Islamic Economics Study Program were given a questionnaire as part of this quantitative field study. Validity tests, reliability tests, t and f tests, simple linear regression, and classical assumptions were used to assess the data. The analysis's findings indicate that live broadcasting significantly influences consumers' decisions to buy. The resulting regression equation is Y = 10.166 - 0.742X. The hypothesis is supported since the t-value of 10.178 is greater than the t-table of 1.999 and has a significance level of 0.000 (p < 0.05). At 103.584, the F test is likewise significant. The influence of the live streaming variable is indicated by the coefficient of determination (R2) of 62.6%, whilst other elements not included in this research model influence 37.4%.